2008
DOI: 10.1159/000143390
|View full text |Cite
|
Sign up to set email alerts
|

Relation between AT1R Gene Polymorphism and Long-Term Outcome in Patients with Heart Failure

Abstract: Objectives: Angiotensin II plays a key role in the pathophysiology of heart failure (HF). This study examined the angiotensin II type 1 receptor (AT1R) polymorphism in patients with systolic HF and its relation to clinical manifestations and patient outcome. Methods: We genotyped 134 patients with HF and reduced systolic function for the AT1R A1166C genotype using polymerase chain reaction and restriction fragment length polymorphism. We analyzed the relationship between the AT1R A1166C polymorphism and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Polymorphism AT1R 1166C has been studied in relation to diastolic HF, 13 coronary artery disease 17 and incidence of HF. 10 , 18 Wu, et al . 13 reported that AT1R 1166C carriers were associated with a higher risk of diastolic HF, and Mishra, et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymorphism AT1R 1166C has been studied in relation to diastolic HF, 13 coronary artery disease 17 and incidence of HF. 10 , 18 Wu, et al . 13 reported that AT1R 1166C carriers were associated with a higher risk of diastolic HF, and Mishra, et al .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, two further studies failed to find any significant relationship between A1166C polymorphisms and incidence of HF. 10 , 18 …”
Section: Resultsmentioning
confidence: 99%
“…Based on the inclusion criteria, only 5 case-control studies (Gubaev et al, 2006;Amir et al, 2009;Zakrzewski-Jakubiak et al, 2008;Wu et al, 2008;Cameron et al, 2006) with full-text were included in this metaanalysis and 28 studies were excluded. The flow chart of study selection is summarized in Figure 1.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…The published year of the studies included ranged from 2006 to 2014. The study characteristics are presented in Table 1, and contain the population studies of 4 Caucasians (Gubaev et al, 2006;Zakrzewski-Jakubiak et al, 2008;Cameron et al, 2006) and 2 Asians (Amir et al, 2009;Cameron et al, 2006). The source of the controls was based on healthy populations.…”
Section: Characteristics Of the Studies Includedmentioning
confidence: 99%
“…In particular, a SNP has been described in which there is an A/C transversion at position +1166 (i.e., 1166 base-pairs downstream from the start codon, dsSNP# rs5186) located in the 3′-UTR of the hAT 1 R gene. The increased frequency of the +1166 C-allele has been associated with hypertension [108115], cardiac hypertrophy [116118], aortic stiffness [119121], myocardial infarction [122], heart failure [123125], abdominal aortic aneurysms [126, 127], and increased oxidative stress levels in human heart failure [128]. However, the physiological relevance of this polymorphism is uncertain because of its location within the noncoding region of the hAT 1 R gene.…”
Section: The Human At1r Gene and Mirsnpsmentioning
confidence: 99%